Evaluating the Difference Between COVID-19-Associated Telogen Effluvium and Telogen Effluvium Due to Other Causes - Didem Kazan; Defne Ozkoca; Nazlı Dizen Namdar (Mattioli1885, 2024)
Introduction: Telogen effluvium (TE) is a common type of non-cicatricial alopecia, and it is reported frequently in patients with SARS-CoV-2 infection. Objectives: Herein, we aimed to examine the demographic, dermoscopic, and laboratory features of the patients with SARS-CoV-2 associated TE (CATE) and compare them with TE due to other causes (TEDOC) according to these features. Methods: In this retrospective case-control study we evaluated the patients who were diagnosed with TE and were above 18 years of age between April and June 2022. The patients were divided into two groups based on their medical history and SARS-CoV-2 PCR positivity. The first group included patients with CATE and positive SARS-CoV-2 PCR test results in the last 3 months. The second group consisted of patients with TEDOC. Patients' gender, age, disease duration, additional systemic disease, dermoscopic findings, and laboratory results were recorded. Results: A total of 92 patients, 86 (93.5%) female, and 6 (6.5%) male, were included in the study. CATE was detected in 52 (56.5%) patients whereas 40 (44.5%) patients had TEDOC. The mean time between the onset of SARS-CoV-2 infection and hair loss complaint was calculated as 64.8 + 25.6 days, and this time was significantly shorter than patients with TEDOC (p=0.003). The dermoscopic evaluation showed that empty follicular openings and yellow dots were statistically higher in patients with CATE, whereas short regrowing hair were markedly higher in patients with TEDOC. (p=0.001, p=0.001, and p=0.001, respectively) Conclusions: CATE is characterized by excessive hair-shedding that begins sooner after infection than classic TE. Dermoscopic findings can assist clinicians in diagnosis.